2022
DOI: 10.1007/s40145-022-0627-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cathodic activity by tantalum inclusion at B-site of La0.6Sr0.4CO0.4Fe0.6O3 based on structural property tailored via camphor-assisted solid-state reaction

Abstract: Lanthanum strontium cobalt ferrite (LSCF) is an appreciable cathode material for solid oxide fuel cells (SOFCs), and it has been widely investigated, owing to its excellent thermal and chemical stability. However, its poor oxygen reduction reaction (ORR) activity, particularly at a temperature of ⩽ 800 °C, causes setbacks in achieving a peak power density of > 1.0 W·cm−2, limiting its application in the commercialization of SOFCs. To improve the ORR of LSCF, doping strategies have been found useful. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Compare with fresh samples the powders calcined at 1300°C just exhibited slightly different crystallinity and had no effect on the conductivity test. 41 The electrical conductivity of LSF and LSF8 samples in an oxidizing atmosphere and reducing atmosphere both reveal a transition from semiconductor-like to metal-like behavior 42 , 43 , 44 ( Figures 2 C and S7 ), i.e., the electrical conductivity first increases with increasing temperature until it reaches a maximum, then decreases with temperature subsequently. In addition, the electrical conductivity of RP-LSF is almost negligible compared to LSF.…”
Section: Resultsmentioning
confidence: 98%
“…Compare with fresh samples the powders calcined at 1300°C just exhibited slightly different crystallinity and had no effect on the conductivity test. 41 The electrical conductivity of LSF and LSF8 samples in an oxidizing atmosphere and reducing atmosphere both reveal a transition from semiconductor-like to metal-like behavior 42 , 43 , 44 ( Figures 2 C and S7 ), i.e., the electrical conductivity first increases with increasing temperature until it reaches a maximum, then decreases with temperature subsequently. In addition, the electrical conductivity of RP-LSF is almost negligible compared to LSF.…”
Section: Resultsmentioning
confidence: 98%
“…2,3 Among these methods, solid oxide electrolysis cells (SOECs) in water electrolysis technology operate at relatively high temperatures and have demonstrated potential for more efficient hydrogen production compared to alkaline and polymer electrolysis systems. [4][5][6][7] While numerous studies have reported the high performance of water electrolysis, ensuring the long-term stability of SOECs remains a challenge. 8 Efforts to mitigate degradation are crucial for developing highly efficient water electrolysis systems.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] However, owing to the deficient protonconducting properties of MIEC cathode materials, the active site of cathodes is limited to a triple-phase boundary (TPB), which is the interface between cathodes and electrolytes. [11][12][13][14] Therefore, one of the basic requirements for highly active PCFC cathodes is the ability of conducting O 2− , H + , and e − at the same time, extending the active site to the entire cathode. [11,[15][16][17]18] Duan et al developed a new type of highly active triple conductive material, BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 3−𝛿 (BCFZY), for PCFC cathodes, which showed excellent performance at medium temperatures (e.g., the area-specific resistance (ASR) was only 0.09 Ω cm 2 at 600 °C).…”
Section: Introductionmentioning
confidence: 99%
“…[ 3–10 ] However, owing to the deficient proton‐conducting properties of MIEC cathode materials, the active site of cathodes is limited to a triple‐phase boundary (TPB), which is the interface between cathodes and electrolytes. [ 11–14 ] Therefore, one of the basic requirements for highly active PCFC cathodes is the ability of conducting O 2− , H + , and e − at the same time, extending the active site to the entire cathode. [ 11,15–17,18 ]…”
Section: Introductionmentioning
confidence: 99%